THE EFFECT OF RELIGIOSITY, THE LEVEL OF INCOME, AND THE LEVEL OF ISLAMIC FINANCIAL LITERACY TOWARD THE INTEREST OF STUDENT TO BECOME CUSTOMERS IN SHARIA FINANCIAL INSTITUTION - Luthfiani, Rifda Amalia; Sari, Ratna Candra (Universitas Negeri Yogyakarta, 2019)
Abstract : The Effect of Religiosity, The Level of Income, and The Level of Islamic Financial Literacy Toward The Interest Of Student To Become Customers In Sharia Financial Institution. This research aims to analyze (1) the effect of religiosity toward the interest of students to become customers in Sharia financial institutions, (2) the effect of income on the interest of students to become customers in Sharia financial institutions, (3) the effect of the level of Islamic financial literacy the interest of students to become customers in Sharia financial institutions, and (4) the effect of religiosity, income, and the level of Islamic financial literacy the interest of students to become customers in Sharia financial institutions.This research was causal research, used a purposive sampling method, and used multiple linear regression technique. The results of this research indicate that all independent variables have a positive effect on the dependent variable. Keywords : The Interest of Students to Become Customers in Sharia Financial Institutions, Religiosity, The Level of Income, The Level of Islamic Financial Literacy